2018
DOI: 10.1007/s11420-018-9622-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Re-admission and Emergency Department Visits Within 90 Days Following Lower-Extremity Arthroplasty

Abstract: We identified demographic and procedure-related variables associated with an increased risk of ED visits and inpatient re-admissions after TKA or THA. Understanding these variables will contribute to improved care quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…16 For sports medicine procedures, a recent study by Brown et al reported an unplanned medical care utilization rate of 0.75% within the 24-hour postoperative period, 30 which is lower than the ED utilization rates in this study but is primarily representative of the immediate postoperative period. Of note, postoperative ED utilization rates for sports-related injuries were markedly lower than the 4.5 to 13.8% reported in the total joint arthroplasty literature, 12,[21][22][23][24] which can be partially explained by the invasive nature of joint arthroplasty procedures and their higher postoperative pain and complication profiles. Regarding postoperative readmissions rates, only 0.9% (15/1729) of all postoperative ED visits resulted in a subsequent inpatient admission, with preexisting hypertension as a major risk factor for hospitalization.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…16 For sports medicine procedures, a recent study by Brown et al reported an unplanned medical care utilization rate of 0.75% within the 24-hour postoperative period, 30 which is lower than the ED utilization rates in this study but is primarily representative of the immediate postoperative period. Of note, postoperative ED utilization rates for sports-related injuries were markedly lower than the 4.5 to 13.8% reported in the total joint arthroplasty literature, 12,[21][22][23][24] which can be partially explained by the invasive nature of joint arthroplasty procedures and their higher postoperative pain and complication profiles. Regarding postoperative readmissions rates, only 0.9% (15/1729) of all postoperative ED visits resulted in a subsequent inpatient admission, with preexisting hypertension as a major risk factor for hospitalization.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies evaluated ED utilization after elective hip arthroplasty, 15 outpatient hand surgery, 16 rotator cuff repair, 17 ankle surgery, [18][19][20] and total joint arthroplasty. 12,[21][22][23][24] Common findings among these studies found low overall postoperative ED utilization rates with postoperative pain as the most common reason for visit and Medicare and Medicaid insurance status as preoperative risk factors. [15][16][17]24 However, there was limited information about the epidemiology of postoperative ED utilization for procedures treating sports-related injuries.…”
mentioning
confidence: 99%
“…Our study revealed that 19.9% of patients visited the ED within 90 days. A large cohort study with 200,645 patients revealed that the incidence of unplanned ED return after total knee arthroplasty (TKA) and total hip arthroplasty (THA) within 90 days was 5.2% and 4.6%, respectively [ 12 ]. Another systematic review showed that the average ED visit rate within 90 days after total joint arthroplasty (TJA) was 10.3% (0–33%), with 10.8% for TKA and 9.7% for THA [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients operated on according to ERAS protocols with early discharge from the hospital have long been considered at risk of subsequent re-admission, typically for surgical site infection, dislocation, deep vein thrombosis, or symptomatic anemia [ 139 ]. However, current evidence [ 140 ] shows that ERAS protocols are not relevant to re-admission rates.…”
Section: Discussionmentioning
confidence: 99%
“…Early function and mobilization are key factors for the success of a short-stay program, and recent Fast Track guidelines recommend that patients should be mobilized as soon as possible after surgery [ 23 ]. Mobilization on the day of surgery has gained importance in reducing LOS without increasing the rate of immediate adverse events, regardless of age, BMI, and ASA score [ 134 , 135 , 136 , 137 , 138 , 139 , 140 ]. Patients should be informed and educated about the postoperative physiotherapy progression: from isometric muscle contraction to assisted verticalization to ambulation with aids, and finally to climbing and descending stairs independently.…”
Section: Post-operative Optimizationmentioning
confidence: 99%